The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.celrep.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The Drug Vehicle and Solvent N-Methylpyrrolidone Is an Immunomodulator and Antimyeloma Compound

Abstract: N-methyl-2-pyrrolidone (NMP) is a common solvent and drug vehicle. We discovered unexpected antineoplastic and immunomodulatory activity of NMP in a cMYC-driven myeloma model. Coincident to this, NMP was identified as an acetyllysine mimetic and candidate bromodomain ligand. Accordingly, NMP-treated cells demonstrated transcriptional overlap with BET-bromodomain inhibition, including downregulation of cMYC and IRF4. NMP's immunomodulatory activity occurred at sub-BET inhibitory concentrations, and, despite phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 39 publications
3
35
0
Order By: Relevance
“…Due to this characteristic, NMP can be considered a low affinity bromodomain inhibitor. These results are consistent with the recently published data showing that NMP is a functional acetyl lysine mimetic molecule [17,27].…”
Section: Discussionsupporting
confidence: 83%
“…Due to this characteristic, NMP can be considered a low affinity bromodomain inhibitor. These results are consistent with the recently published data showing that NMP is a functional acetyl lysine mimetic molecule [17,27].…”
Section: Discussionsupporting
confidence: 83%
“…Our result is in line with recently published paper showing that NMP possess an immunomodulatory activity [29].…”
Section: Discussionsupporting
confidence: 83%
“…In fact, Shortt at al. showed that NMP is a functional lysine mimetic molecule [29]. Moreover, JQ1 a potent inhibitor of BRD2, BRD3, BRD4 and BET, was shown to suppress inflammation by a reduction of the inflammatory cytokine release and bone destruction by the inhibition of osteoclast maturation [30].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that this common laboratory solvent can act as a weak affinity, broad spectrum bromodomain inhibitor with binding demonstrated to multiple bromodomains including BET. In a mouse model of myeloma, treatment with NMP demonstrated antineoplastic and immunomodulatory activity consistent with BET inhibition [21].…”
Section: Bet Bromodomain Inhibitors In Clinical Trialsmentioning
confidence: 94%